(5-n-Butyl-10,20-diisobutylporphyrinato)nickel(II). - SENGE, MATHIAS (My University, 2014)
The asymmetric unit of the title compound, [Ni(C 32 H 36 N 4 )], contains two independent molecules exhibiting an overall ruffled conformation of the porphyrin macrocycle and differing mainly in the positions of the methyl groups. The average Ni—N bond lengths are 1.912 (2) and 1.910 (2) A ̊ in the two molecules. The molecules form a closely spaced lattice structure in which neighbouring porphyrins are oriented in a nearly perpendicular fashion to each other. The compound was prepared via nucleophilic substitution of (5,15-diisobutyl- porphyrinato)nickel(II) with n -butyllithium
PUBLISHED
Keywords: [Ni(C 32 H 36 N 4 )]; [Ni(C 32 H 36 N 4 )]